OBIA CLASSIFICATION AND BUILT-UP LAND INDICES NDBI FOR ESTIMASTION OF SETTLEMENT DENSITY IN PONTIANAK CITY - Trida Ridho Fariz (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Settlement density data is very important because the density of settlements is one of the main indicators of slum settlement in Pontianak City. The one of way to obtain settlement density information is to use remote sensing data like satellite imagery or aerial photo. This is a problem considering the budget and more time to get high resolution satellite imagery and extract the information we want.The one method for the detection of settlements using Landsat 8 satellite imagary is the built-up land indices NDBI (Normalized Difference Build-up Index). Objective of this research is build spatial model of settlement density in Pontianak City using built-up land indices NDBI (Normalized Difference Build-up Index), moreover combining with OBIA Classification (Object Base Image Analysis).The results of this research indicate that built-up land indices NDBI has a value of determination (R2) is high that is equal to 0.628 and has a strong correlation of 0.792 to the density of settlements calculated from aerial photo. The spatial model of settlement density estimation has a R2 of 0.75 and a RMSE value of 5.10